2021
DOI: 10.1111/nph.17170
|View full text |Cite
|
Sign up to set email alerts
|

Stage‐specific regulation of purine metabolism during infectious growth and sexual reproduction in Fusarium graminearum

Abstract: Summary Ascospores generated during sexual reproduction are the primary inoculum for the wheat scab fungus Fusarium graminearum. Purine metabolism is known to play important roles in fungal pathogens but its lifecycle stage‐specific regulation is unclear. By characterizing the genes involved in purine de novo and salvage biosynthesis pathways, we showed that de novo syntheses of inosine, adenosine and guanosine monophosphates (IMP, AMP and GMP) are important for vegetative growth, sexual/asexual reproduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 75 publications
(112 reference statements)
0
21
0
Order By: Relevance
“…Matching metabolites related to purine ring from "Caffeine biosynthesis" highlight triggering of nitrogen reservoir during FHB in wheat as was previously observed [99]. Adenosine, guanosine and their phosphorylated forms of IMP, AMP and GMP are critical metabolites for vegetative growth, sexual/asexual reproduction and pathogenesis in F. graminearum [100]. In addition, adenine phosphoribosyltransferase has been reported as critical in enhancing oxidative stress tolerance in A. thaliana [101].…”
Section: Genotype-specific Metabolomic Response To Fhbmentioning
confidence: 52%
“…Matching metabolites related to purine ring from "Caffeine biosynthesis" highlight triggering of nitrogen reservoir during FHB in wheat as was previously observed [99]. Adenosine, guanosine and their phosphorylated forms of IMP, AMP and GMP are critical metabolites for vegetative growth, sexual/asexual reproduction and pathogenesis in F. graminearum [100]. In addition, adenine phosphoribosyltransferase has been reported as critical in enhancing oxidative stress tolerance in A. thaliana [101].…”
Section: Genotype-specific Metabolomic Response To Fhbmentioning
confidence: 52%
“…In the presence of combined stress, a single pathway related to purine nucleotide production and degradation was enriched. It has been shown that biosynthesis and degradation of purine nucleotides play an essential role in the growth and virulence of various fungal communities; microbial communities might be using these pathways for better growth and survival under combined stress (105,106). Microbial function in the ecosystem is determined not just because of the number and composition of taxa but because of the various positive, negative, direct, or indirect associations among the community members (107).…”
Section: Given the Impact Of Altered [O3] Resulting In A Possible Com...mentioning
confidence: 99%
“…Matching metabolites related to purine rings from ”Caffeine biosynthesis” highlighted the triggering of nitrogen reservoirs during FHB in wheat, as was previously observed [ 76 ]. Adenosine, guanosine, and their phosphorylated forms of IMP, AMP, and GMP are critical metabolites for vegetative growth, sexual/asexual reproduction, and pathogenesis in F. graminearum [ 77 ]. Some transcripts encoding enzymes from purine metabolism were reported to be FHB-resistance-related in wheat [ 78 ].…”
Section: Discussionmentioning
confidence: 99%